Nuclear binding energy and density distribution of Pb isotopes in a Skyrme - Hartree - Fock method - Y. Yulianto; Z. Su’ud; Department of Physics, Bandung Institute of Technology, Bandung, Indonesia (Ядерна фізика та енергетика)
In this study, nuclear ground-state properties of spherical nuclei, such as the total energy, nucleon local density, and nucleon local potential of Pb isotopes (especially 204-214Pb) are investigated by using Hartree - Fock method. The calculations have been performed by using Skyrme set parameters, especially SLy4, SkM*, Zσ, and SIII set parameters. The calculation results have been compared to the related experiment results and the calculation results of the other researchers. All parameters used in this study are in good agreement with the results of the related experiments and the other researchers. In Pb nucleus, it is also obtained from this study that the total energy, mass radius, neutron radius, neutron skin thickness, neutron density, neutron density width, proton potential depth, and proton potential width increase accordingly with the increase of neutron number. In other hand, proton density and neutron potential decrease accordingly with the increase of neutron number. The increase of neutron number has minimum effect to the widths of proton density and neutron potential.